An evaluation of muhadatsah program at Pondok Modern Daarul Abror using CIPP Model - Fitriyani Fitriyani (Universitas Sarjanawiyata Tamansiswa, 2020)
This research aimed to describe the evaluation of Muhadatsah Program in English teaching and learning process in Pondok Modern Daarul Abror in terms of the context, input, process, and product aspects. This research is evaluation research employing the CIPP model by Stufflebeam (2007). The data were collected through observation, interview, document analysis, and audio-visual materials. The data were analyzed using Miles and Humberman (1994)â€™s flow model of qualitative data research which included data reduction, data display, and conclusion and verification. In the term of product, the evaluation showed that MP can improve their vocabulary. It helped them in learning English in the classroom especially in writing and reading, they could speak English fluently and bravely, they knew how to pronounce the word correctly and the intonation of the sentence. It can make them speak up bravely.Â However, it still needs improvement because the students who join MP just follow the rule but they didnâ€™t realize the importance of language for them.